Anger and Repair: The Art and Politics of Judy Watson's the holes in the land (2015). Issue 1 (2nd January 2018) - Best, Susan
Abstract: This article examines the six coloured etchings in the series, the holes in the land (2015), by Australian Indigenous artist Judy Watson. The series resulted from a residency in the British Museum in 2013 where Watson had access to Aboriginal artefacts from near to her country in north-west Queensland. Watson is a Waanyi artist with maternal ties to north-west Queensland. I analyse the series as ground-breaking in a number of important ways. First, the tone of her visually seductive work departs from the norm of anger proposed as the dominant affect in urban Aboriginal art by Ian McLean. Secondly, the series has the kind of complex ambivalence so well described by Eve Kosofsky Sedgwick in her account of reparative approaches to cultural material. And finally, Watson's vibrant and engaging way of representing the land aligns her with the tenets of Walter Mignolo's decolonial approach.